Evaluating the role of fish as surrogates for amphibians in pesticide ecological risk assessment. (November 2019) - Glaberman, Scott; Kiwiet, Jean; Aubee, Catherine B.
Abstract: Ecological risk of chemicals to aquatic-phase amphibians has historically been evaluated by comparing estimated environmental concentrations in surface water to surrogate toxicity data from fish species. Despite their obvious similarities, there are biological disparities among fish and amphibians that could affect their exposure and response to chemicals. Given the alarming decline in amphibians, in which anthropogenic pollutants play at least some role, investigating the risk of chemicals to amphibians is becoming increasingly important. Here, we evaluate relative sensitivity of fish and larval aquatic-phase amphibians to 45 different pesticides using existing data from three standardized toxicity test designs: (1) amphibian metamorphosis assay (AMA) with the African clawed frog ( Xenopus laevis ); (2) fish short-term reproduction assay (FSTRA) with the fathead minnow ( Pimephales promelas ); (3) fish early life stage test (ELS) with fathead minnows or rainbow trout ( Oncorhynchus mykiss ). The advantage of this dataset over previous work is that the underlying studies are consistent in exposure method, study duration, test species, endpoints measured, and number of concentrations tested. We found very strong positive relationships between fish and frog lowest adverse effect concentrations (LOAEC) for survival [Spearman's rank correlation ( r s ) = 0.88], body weight ( r s = 0.86), and length ( r s = 0.89) with only one out of 45 chemicals (propiconazole) exhibiting 100-folder greater sensitivity in frogs relative to fish. While our results suggest comparable toxicity for pesticides between fish and aquatic-phase amphibians under these test conditions, further research with a greater diversity of amphibians and exposure scenarios will help determine the relevance of these results across species and life stages. Highlights: Aquatic-phase amphibians and fish exhibit similar sensitivities to pesticides. Amphibians may be more sensitive than fish to certain fungicides and pyrethroids. Results address use of fish as surrogates for amphibians in regulatory toxicology. More amphibian species should be tested to address fish-amphibian surrogacy.